The FAST-STEMI Network in Biella From 2013 to 2019: Impact of the Delocalization of the Hospital Facilities on Ischemia Time and In-hospital Outcomes. Issue 2 (June 2021) - Verdoia, Monica; Viola, Orazio; D'Amico, Giuseppina; Ravetto, Cinzia; Comoglio, Antonella; Fusco, Massimo; Giachino, Paolo; La Cognata, Sara; Novara, Francesca; Bristot, Filippo; Pipan, Pierpaolo; Magnaghi, Morris; et al.
Abstract : Background: The optimization of the strategies for myocardial revascularization has improved the outcomes of patients with ST-segment elevation myocardial infarction. In Piedmont, the FAST-STEMI regional network was created for improving the management and transportation of ST-segment elevation (STEMI) patients to primary percutaneous coronary intervention facilities, reducing the time to reperfusion. Within this network, the Hospital of Biella was delocalized in December 2014 to a new suburban structure designed for an easier access, which might have shortened the duration of patients' transportation and ischemia, with potential positive prognostic effects. The aim of the present study was to define the impact of the decentralization of the hospital structure on the time to reperfusion and in-hospital outcomes among STEMI patients admitted to the Hospital of Biella. Methods: We included STEMI patients admitted to our urban hospital between 2013 and 2019 and included in the FAST-STEMI database. The primary endpoint was the duration of ischemia, defined as pain to balloon (PTB). The primary outcome endpoint (PE) was in-hospital mortality. Results: We included 276 consecutive patients with STEMI undergoing primary percutaneous coronary intervention between 2016 and 2019 in the new hospital facility, which were compared with 170 patients treated between 2013 and June 2014 in the prior structure. Patients' characteristics included a mean age of 67.5 ± 12.5 years, 72.1% males and 18.7% patients with diabetes. In the new facility, the median PTB was 188 minutes [interquartile range: 125–340 min], reduced as compared with the period 2013–2014 [215 (128.5–352 min), P = 0.002]. The median in-hospital stay was also shorter ( P = 0.004), whereas a nonsignificant improvement was noted for ejection fraction (EF) at discharge ( P = 0.14). A linear relationship was demonstrated between PTB and the EF (r = −0.183, P = 0.003) in patients treated between 2016 and 2019 while not affecting the length of hospitalization or in-hospital outcomes. In fact, in-hospital death occurred in 36 patients, 8% in the new structure versus 7.7% in 2013–2014 [hazard ratio (HR) (95% confidence interval [CI]) = 1.20 (0.59–2.42), P = 0.62]. The independent predictors of mortality were patients' age and EF at discharge (age ≥ 75 y: adjusted HR [95% CI] = 6.75 [1.51–30.1], P = 0.01; EF: adjusted HR [95% CI] = 0.91 [0.88–0.95], P < 0.001). Conclusions: The present study shows that, among the STEMI patients treated in our center, the delocalization of the hospital facilities and the optimization of the FAST-STEMI network reduced the duration of ischemia, with positive effects on left ventricular function at discharge. However, this did not translate into a significant benefit in survival, which was instead conditioned by the aging of the population.